Association between the side effect induced by COVID-19 vaccines and the immune regulatory gene polymorphism - Chen, Ding-Ping; Wen, Ying-Hao; Lin, Wei-Tzu; Hsu, Fang-Ping (Frontiers in Immunology, 2022)
People often worry about the side effects after vaccination, reducing the willingness to vaccinate. Thus, we tried to find out the risk of single nucleotide polymorphism (SNP)vaccines, so as to improve the willingness and confidence in vaccination. Allergic and inflammatory reactions are the most common vaccine side effects that are caused by immune system overreaction. Additionally, a previous study showed significantly higher frequency of febrile reactions to measles vaccines in American Indians than in Caucasian children, and it indicated that the side effects varied according to genetic polymorphisms in individuals. Thus, the SNPs of immune regulatory genes, cytotoxic T-lymphocyte-associated protein 4 (CTLA4), CD28, tumor necrosis factor ligand superfamily member 4 (TNFSF4), and programmed cell death protein 1 (PDCD1) were included in this study to analyze the association with vaccine side effects. Additionally, the 61 healthy participants were asked how many doses they received, the brand of the vaccine, and the side effects they suffered. We found that several SNPs were associated with side effects after the first or second dose of mRNA vaccines or adenoviral vector vaccine vaccination. Additionally, these SNPs were also associated with several autoimmune diseases and cancers, so they must play an important role in immune regulation. Moreover, it was found that the rs3181096 and rs3181098 of CD28, the rs733618 and rs3087243 of CTLA4, and the rs1234314 of TNFSF4 were associated with mild vaccine side effects induced by mRNA vaccines and adenoviral vector vaccine that would play a potential role in vaccine-induced immune responses and may further lead to fetal side effects. These results could be served as a basis for investigating the mechanisms of vaccine side effects. Furthermore, it was hoped that these results would address the public's concerns about the side effects of the COVID-19 vaccination. In clinical application, a rapid screening test can be carried out to assess the risk of vaccine side effects before vaccination and give treatment as soon as possible